Associations between Gut Microbiota and Intestinal Inflammation, Permeability and Damage in Young Malawian Children. (12th February 2022) - Kortekangas, Emma; Fan, Yue-Mei; Chaima, David; Lehto, Kirsi-Maarit; Malamba-Banda, Chikondi; Matchado, Andrew; Chingwanda, Chilungamo; Liu, Zhifei; Ashorn, Ulla; Cheung, Yin Bun; Dewey, Kathryn G; Maleta, Kenneth; et al.
Abstract: Background: Environmental enteric dysfunction (EED) is common in low- and middle-income countries and associated with childhood undernutrition. The composition of gut microbiota has been implicated in the pathogenesis of EED. Our aim was to assess the associations between gut microbiota and EED biomarkers in rural Malawian children. We hypothesized that there would be an inverse association between microbiota maturity and diversity and fecal concentrations of EED biomarkers. Methods: We used data from fecal samples collected at 6, 18 and 30 months from 611 children who were followed up during a nutrition intervention trial. The primary time point for analysis was 18 months. Microbiota data were obtained through 16S rRNA sequencing and variables included microbiota maturity and diversity, phylogenetic dissimilarity and relative abundances of individual taxa. EED biomarkers included calprotectin (marker of inflammation), alpha-1 antitrypsin (intestinal permeability) and REG1B (intestinal damage). Results: There was an inverse association between microbiota maturity and diversity and fecal concentrations of all 3 EED biomarkers at 18 months ( p ≤0.001). The results were similar at 30 months, while at 6 months inverse associations were found only with calprotectin and alpha-1 antitrypsin concentrations. At 18 months, EED biomarkers were not associated with phylogenetic dissimilarity, but at 6 and 30 months several associations were observed. Individual taxa predicting EED biomarker concentrations at 18 months included several Bifidobacterium and Enterobacteriaceae taxa as well as potentially displaced oral taxa. Conclusions: Our findings support the hypothesis of an inverse association between microbiota maturity and diversity and EED in rural Malawian children. Lay Summary: Chronic childhood undernutrition is an important public health concern that affects about 150 million children, mostly in low- and middle-income countries. Undernutrition is caused by insufficient nutrient intake and frequent infections, but there are also other underlying factors. One of these is a condition called environmental enteric dysfunction (EED), which is characterized by intestinal inflammation and damage without apparent clinical symptoms. EED is thought to be caused by the ingestion of pathogenic bacteria that leads to changes in the intestine such as increased permeability and decreased absorptive capacity. This might make the intestinal wall vulnerable to bacterial invasion and reduce the absorption of nutrients. Besides potentially pathogenic bacteria, there are many commensal bacteria in the gastrointestinal tract that have beneficial functions and that interact with the immune system. The aim of our study was to assess the associations between all these bacteria, that is the intestinal microbiota and biomarkers of EED. We used data from fecal samples collected from young children participating in a nutrition intervention trial in rural Malawi. Our findings support an inverse association between the diversity and maturity of the intestinal microbiota and biomarkers of EED. Additionally, we identified the differences at the level of individual bacterial taxa (groups of bacteria defined by genetic similarity) between participants with different levels of EED biomarkers. Due to the type of study, we cannot determine whether the observed associations represent a causal relationship between the intestinal microbiota and EED. This as well as the exact mechanisms behind these associations should be assessed in further studies.